Hubungan Pengetahuan dan Sikap Tenaga Pelayanan Medis Terhadap Perilaku Pemilahan Sampah Medis Padat di UPT RSUD Bali Mandara Provinsi Bali - Sri Indah Pramana Widayani; Nyoman Ngurah Adisanjaya; Ni Putu Widya Astuti (HIGIENE: Jurnal Kesehatan Lingkungan, 2019)
Hospital waste consists of medical waste and domestic waste. Medical waste has the potential to pollute the environment and can cause disease pollution. Medical personnel are particularly vulnerable to the risk of occupational exposure and diseases. This study was conducted to determine the Relationship between Knowledge and Attitudes of Medical Services Personnel to the Medical Waste Sorting Behavior at UPT RSUD Bali Mandara Provinsi Bali.This study uses a cross sectional study design by observing and interviewing based on the questionnaire. Data collection was carried out at the same time to find out the relationship between the independent variables and the dependent variables studied. The results obtained were then processed using the Chi Square test. Obtained a significant value (sig) for the knowledge variable is 0.00 and a sig value for the attitude variable is 0.00 which means the value of sig < 0.05 means that the hypothesis or Ho is rejected.So it can be concluded that the knowledge and attitude of Medical Service Personnel has a strong influence on the behavior of Solid Medical Waste Sorting at UPT RSUD Bali Mandara Provinsi Bali. In connection with the results of the research obtained, medical service personnel require the provision and provision of material accompanied by an evaluation relating to the management system of solid medical waste in hospitals. Keywords: Medical Services, Behavior, Waste Sorting, Solid Medical Waste